2014
DOI: 10.1007/s40009-014-0280-1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hierarchical Technique for Offline Handwritten Gurmukhi Character Recognition

Abstract: The increasing need of a handwritten character recognition system in the Indian offices such as banks, post offices and so forth, has made it an imperative field of research. In present paper, Authors have presented a novel hierarchical technique for isolated offline handwritten Gurmukhi character recognition. A robust feature set of 105 feature elements is proposed under this work for recognition of offline handwritten Gurmukhi characters using four types of topological features, namely, horizontally peak ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Kumar et al [7] have presented efficient feature extraction techniques for offline handwritten Gurmukhi character recognition. They have also presented a hierarchical technique for offline handwritten Gurmukhi character recognition [5]. Using this technique, they accomplished a recognition accuracy of 91.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [7] have presented efficient feature extraction techniques for offline handwritten Gurmukhi character recognition. They have also presented a hierarchical technique for offline handwritten Gurmukhi character recognition [5]. Using this technique, they accomplished a recognition accuracy of 91.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [24] used diagonal features, centroid features, horizontal peak extent and vertical peak extent features with hierarchical zoning (similar to proposed work) for offline handwritten Gurmukhi character recognition. They experimented with different combinations for features.…”
Section: Resultsmentioning
confidence: 99%
“…The zoning feature extraction technique divides the character image into n number of regions in hierarchical arrangement as proposed by Kumar et al (2014). Suppose an input image is at current level L and then it is having 4 (L) sub-images.…”
Section: Feature Extractionmentioning
confidence: 99%
“…These feature extraction approaches have been evaluated by numerous researchers for distinct script identification, and it has been observed that these approaches are accomplishing recommendable results as compared to other approaches specified for handwriting recognition (Kumar et al 2013a, b). Initially, each input image is partitioned into n number of uniform sized zones for extracting various features (Kumar et al 2014). Depending on the four features specified, three classification techniques, namely, convolution neural network (CNN), decision tree and random forest are used for the classification of input characters.…”
Section: Introductionmentioning
confidence: 99%